Gender differences in absence from work: Lessons from two world wars - Tobias Karlsson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
This paper traces the origins and early history of perceived gender differences in absenteeism in Great Britain and the USA. Among politicians and scholars, the problem was first articulated during World War I and reappeared as an issue of prime concern during World War II. The war efforts required mobilization and allocation of large numbers of women to jobs that had previously been done by men while maintaining high and continuous flows of production in an economy that was increasingly characterized by high capital intensity. The most common explanation of women's higher levels of absenteeism was their double burden of wage work and unpaid household duties. Although researchers in the field were cautious to give policy recommendations, the studies on absenteeism revealed that 'industrial fatigue' could have negative effects on productivity and helped to motivate regulations on working hours. Studies on absenteeism also encouraged firms to professionalize personnel management and to reinforce apprehensions of differences between men and women as workers and employees. Some employers and other policy makers referred to gender differences in absenteeism to motivate wage discrimination.
Keywords: H56; J16; M54; N32; N34; N42; N44; 330; absenteeism; gender; Great Britain; United States; World War I; World War II